Tweeted twitter.com/StackPhilosophy/status/1031375642338701312
2 restated question in title, reformating
source | link

How to prove the following¬¬(A ∨ B) leads to ¬¬(B ∨ A)?

Using laws of natural deduction, how can one prove that the single premise ~~¬¬(AvBA ∨ B) leads to ~~¬¬(BvAB ∨ A).?

I have tried solving the problem for some time but to no avail.

How to prove the following

Using laws of natural deduction, how can one prove that the single premise ~~(AvB) leads to ~~(BvA). I have tried solving the problem for some time but to no avail.

How to prove ¬¬(A ∨ B) leads to ¬¬(B ∨ A)?

Using laws of natural deduction, how can one prove that the single premise ¬¬(A ∨ B) leads to ¬¬(B ∨ A)?

I have tried solving the problem for some time but to no avail.

1
source | link

How to prove the following

Using laws of natural deduction, how can one prove that the single premise ~~(AvB) leads to ~~(BvA). I have tried solving the problem for some time but to no avail.